2016
DOI: 10.1164/rccm.201506-1256oc
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Functional Recovery among Older Intensive Care Unit Survivors

Abstract: Rationale: Most of the 1.4 million older adults who survive the intensive care unit (ICU) annually in the United States face increased disability, but little is known about those who achieve functional recovery.Objectives: Our objectives were twofold: to evaluate the incidence and time to recovery of premorbid function within 6 months of a critical illness and to identify independent predictors of functional recovery among older ICU survivors.Methods: Potential participants included 754 persons aged 70 years o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
117
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 125 publications
(120 citation statements)
references
References 53 publications
3
117
0
Order By: Relevance
“…33 In older patients, higher BMI at the time of hospital admission is associated with better functional outcomes after an ICU admission. 34 We suspect that this is a phenomenon specific to low muscle mass among vulnerable elders, whereas the ALTOS survivor population was generally a younger population (median (IQR) of age=50 (40, 58) years). In general, reduction in BMI has been associated with improvement in QOL, but this is not well studied among ICU survivors.…”
Section: Discussionmentioning
confidence: 98%
“…33 In older patients, higher BMI at the time of hospital admission is associated with better functional outcomes after an ICU admission. 34 We suspect that this is a phenomenon specific to low muscle mass among vulnerable elders, whereas the ALTOS survivor population was generally a younger population (median (IQR) of age=50 (40, 58) years). In general, reduction in BMI has been associated with improvement in QOL, but this is not well studied among ICU survivors.…”
Section: Discussionmentioning
confidence: 98%
“…Increasing evidence suggests that neuromuscular weakness developing from critical illness is independently associated with morbidity and mortality, and is therefore an attractive therapeutic target (Ali et al 2008; Hermans et al 2014). While it has been suggested that older patients exhibit increased the severity of ICU acquired neuromuscular weakness, this has been understudied and the mechanisms are unknown (Ehlenbach et al 2015; Ely et al 2002; Ferrante et al 2015; Ferrante et al 2016). In this manuscript, we present a model of an age-associated increase in mortality from lung injury, coupled with prolonged neuromuscular dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…This ICU - acquired weakness (ICUAW) is attributed to the inflammation, prolonged bed rest, medical/surgical interventions and therapeutics [35] associated with critical illness, and results in the loss of functional independence [6,7] and reduced quality of life [8]. These patients’ weakness is associated with greater disability [9], extended hospitalization [10], prolonged mechanical ventilation (PMV) [11,12] and increased post-ICU mortality [13,14] making their management challenging when transferred to long term acute care hospitals (LTACHs) for physical rehabilitation and ventilator weaning.…”
Section: Introductionmentioning
confidence: 99%